IMMIGRATION INTELLIGENCE OPTIMIZATION RELATED TO INVESTIGATION OF FOREIGN CASES WITHOUT IMMIGRATION DOCUMENTS IN THE WORKING AREA OF IMMIGRATION OFFICE CLASS I TPI BANDUNG - Arsyad Imam Baihaqi; Tony Mirwanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Abstract : Many of the foreigners have activities either for work or tourism in the Bandung area and its surroundings, this of course has an impact on the security and order that exists in the area, because the more activities carried out, the impact caused by these activities will also increase. So it needs a preventive effort through intelligence activities, namely intelligence investigations. The implementation of intelligence investigations in the form of an intelligence cycle at the Class I Immigration Office TPI Bandung which has not been implemented optimally, so that it does not produce an intelligence product. This research focuses on the implementation of intelligence investigations which focuses on intelligence cycle activities and looks through the factors that influence law enforcement. This is what makes the formulation of the problem in this study related to the implementation of the intelligence function in immigration intelligence investigations related to foreigners without immigration documents and efforts to optimize immigration intelligence investigations based on factors that influence law enforcement. The research method used is normative-empirical based on intelligence cycle theory and law enforcement. So the authors draw conclusions based on the results of interviews, field observations, and literature studies, namely intelligence investigation activities in the form of intelligence cycles at the Immigration Office Class I TPI Bandung have been carried out but not optimal, as well as optimization efforts in view of the factors influencing law enforcement which are carried out by increasing means and facilities either through Human Resources or other supporting equipment, as well as forming derivative regulations namely implementing guidelines related to immigration intelligence investigations to support the implementation of intelligence activities. Keyword : Intelligence Investigation, Intelligence Cycle, Law Enforcement